Effect of Surfactant on controlling the Size of Octadecylamine-based Solid Lipid Nanoparticles and Toxicity - Ceren, Kirmizitas Fatma; Sevgi, Varli Hanife; Murat, Demirbilek; Nelisa, Turkoglu (RESEARCH JOURNAL BIOTECHNOLOGY, 2023)
Surfactants play a major role in solid lipid nanoparticles' (SLNs) composition and properties, especially in terms of particle size and zeta potential. Not only the type of the surfactants but also their amounts and chemical compatibility with the lipid core within the formulation cause good changes. In this study, our goal was to determine the effect of tween 80 (a non-ionic surfactant) on octadecylamine (cationic lipid)-based SLN formulation and its influence on SLNs properties. Also, we examined the effect of sonication and filtration as mechanical forces on the particle size, zeta potential and PDI features. Five different formulations were performed by the emulsion solvent evaporation method. Particle size distribution, zeta potential and PDI values were determined by Zetasizer via the dynamic light scattering method. We obtained SLNs resulting from different formulations and one formulation was selected with the most suitable properties for further studies. The stability of the SLNs was examined by incubating them at 4 degrees C in the dark for particular time intervals and the results revealed not only minimal changes in particle size but also no significant changes in zeta potential and PDI values. The nanoparticles were characterized morphologically with Transmission electron microscopy (TEM) and Atomic force microscopy (AFM). The chemical characterization was performed by Fourier-transform infrared spectroscopy (FT-IR). In vitro cytotoxicity via MTT assay on L929 mouse fibroblast cell line was performed and cell viability was determined over 63% for all concentrations.
Keywords: Solid lipid nanoparticles; Octadecylamine; Tween 80; Surfactant; Characterization; FILTRATION EFFICIENCY; PHYSICOCHEMICAL CHARACTERISTICS; SILVER NANOPARTICLES; DRUG-DELIVERY; CRYSTALLIZATION; STABILITY; FILTER; Biotechnology & Applied Microbiology